A statistical study of the errors involved in the sampling and chemical analysis of soils and plants, with particular reference to citrus and pineapples - Steyn, Willem Johannes Abraham (Rhodes University, Faculty of Science, Department of Chemistry, 1958)
1. Accurate and reproducible methods for the determination of N and acid- extractable P in soils are described. The variations in N, P, and K found by intensive sampling of three different soil types are presented. 3. Suggestions for the adequate sampling of soils for various purposes arc given. 4. A study is presented of the preparative stages in leaf analysis (washing, drying, grinding and storage) as applied to citrus and pineapple leaf material. Likely errors are pointed out and procedures whereby these may be minimised are described. 5. A reliable wet-ashing procedure for obtaining leaf solutions is described. 6. Accurate and reproducible methods for the determination of total N, P,. K, Ca, Mg, Na, Fe, Mn, Zn and Cu in citrus and pineapple leaves are presented. 7. It is shown that diurnal variations in nutrient concentrations occur in citrus and pineapple leaves. 8. The variations in N, P, K, Ca, Mg, Na, Fe, Mn, Zn and Cu, occurring from tree to tree in 3 different Navel orange blocks are presented. It is shown that if all these elements are to be represented . to within 10% of the mean values on a 19 : 1 probability level, all the trees in the blocks would have to be sampled. Reasonable sampling procedures for various purposes are suggested. 9. The variations in N, P, K, Ca, Mg, Fe, Mn, Zn and Cu, occurring in 3 different Cayenne pineapple plantations are presented and described. Suitable sampling procedures are suggested.
Keywords: Soil chemistry; Plants -- Analysis; Soils -- Analysis